3D Hierarchical ZnIn2S4 Nanosheets with Rich Zn Vacancies Boosting Photocatalytic CO2 Reduction. (2nd September 2019) - He, Yiqiang; Rao, Heng; Song, Kepeng; Li, Jixin; Yu, Ying; Lou, Yue; Li, Chunguang; Han, Yu; Shi, Zhan; Feng, Shouhua
Abstract: Zinc vacancy (VZn ) is successfully introduced into 3D hierarchical ZnIn2 S4 (3D‐ZIS). The photo‐electrochemical experiments demonstrate that the charge separation and carrier transfer are more efficient in the 3D‐ZIS with rich VZn . Of note, for the first time, it is found that VZn can decrease the carrier transport activation energy (CTAE), from 1.14 eV for Bulk‐ZIS (Bulk ZnIn2 S4 ) to 0.93 eV for 3D‐ZIS, which may provide a feasible platform for further understanding the mechanism of photocatalytic CO2 reduction. In situ Fourier transform infrared (FT‐IR) results reveal that the presence of rich VZn ensures CO2 chemical activation, promoting single‐electron reduction of CO2 to CO2 − . In addition, in situ FT‐IR and CO2 temperature programmed desorption results show that VZn can promote the formation of surface hydroxyl. To the best of current knowledge, there are no reports on the photoreduction of CO2 simply by virtue of 3D‐ZIS with VZn and few literature reports on the photocatalytic reduction of CO2 concerned with CTAE. Additionally, this work finds that surface hydroxyl may play a crucial role in the process of CO2 photoreduction. The work may provide some novel ways to ameliorate solar energy conversion performance and a better understanding of photoreaction mechanisms. Abstract : A greatly enhanced photocatalytic performance is mainly attributed to the zinc vacancy (VZn ) and unique 3D hierarchical structure. Introducing VZn into 3D hierarchical ZnIn2 S4 increases the light response range, accelerates carrier separation and transport, provides more surface active sites, so‐called "hitting three birds with one stone" to enhance photocatalytic efficiency.